Sistem Pendukung Keputusan Penentuan Penerimaan Bantuan Listrik Murah Gratis Menggunakan Metode SAW (Simple Additive Weighting) Pada PT. PLN (Persero) - Pinte Simehate, Sony; Gemasih, Husna; Fitra, AL (Universitas Gajah Putih, 2020)
Information systems today are very important in many fields like education, the institutions - institutions and industry - industry. one of them on Company state-owned PT. PLN (Persero).Issues at PT. PLN (Persero) in terms of determining the beneficiaries free of cheap electricity that is intended for the poor (not capable) is still done manually and decision-making in the determination of beneficiaries have not been effective and easier for officers. So to decision-making becomes more effective and easier for officers, the purpose of assisting in the electricity targeted and given to families in need so as to minimize the possibility of errors in determination of beneficiaries, hence the need to design a decision support system of determining admission electrical power assistance cost free at PT PLN (Persero) with the indicator calculation method Analytichal hierarchy process (AHP) is then the calculation is implemented in an application program through MyAdmin PHP programming language and MySQL database.